A kind of spindle decomposition hardening compound carbide ceramic and preparation method thereof
By aging the composite carbide ceramic block materials at a specific temperature, the problem of difficulty in improving material performance in the prior art is solved, and the mechanical properties of composite carbide ceramics are improved, and the potential for high industrial application is achieved.
Patent Information
- Application Number
- CN202311871589.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-12-29
AI Technical Summary
When the prior art prepares carbide powder into carbide ceramic bulk materials, there is a lack of systematic research on material performance improvement, and the microstructure and structure are difficult to accurately regulate, resulting in the limitations of the strength and other aspects of the complex carbide ceramics and cannot fully utilize their performance advantages.
By aging the composite carbide ceramic bulk material at a specific temperature (1350~1450℃), the amplitude modulation decomposition phenomenon occurs, thereby improving the mechanical properties of the material. The method includes mixing the transition metal source and the carbon source to form a wet gel, drying and heat treatment to obtain a compound carbide powder, followed by rapid hot press sintering and aging treatment.
Through the amplitude modulation decomposition phenomenon after aging treatment, the hardness and mechanical properties of complex carbide ceramics are significantly improved, providing higher industrial application potential.
Smart Images

Figure CN117800733B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing a spinodal decomposition hardening composite carbide ceramic. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At the current stage, complex carbide materials (such as medium-entropy carbides, high-entropy carbides, etc.) have attracted great attention. Their unique structure and properties make them have broad application potential in various fields.
[0004] For example, patent CN 112851352 A (publication date: 2021.05.28) discloses an ultra-high temperature high entropy carbide powder, which is a single-phase solid solution with a rock salt phase structure and a molecular formula of M x C, wherein M is 4-5 of Zr, Ti, Hf, Mo, Ta and Nb. Patent CN 116947497 A (publication date: 2023.10.27) discloses a medium-entropy or high-entropy carbide nanopowder and a preparation method thereof, which ultimately obtains (HfZrTi)C medium-entropy carbide nanopowder and (Ta 0.2 Nb 0.2 Ti 0.2 Zr 0.2 Hf 0.2 )C high entropy carbide nanopowder.
[0005] The above patent only involves the preparation of single-phase composite carbide powder. However, the current process of preparing carbide powder into carbide ceramic bulk material has limitations. There is a lack of systematic research on improving the material performance in bulk form. The microstructure and organization of the material are difficult to be accurately controlled, and the potential performance of the material cannot be fully utilized. As a result, the composite carbide ceramic material finally prepared has limitations in strength and other aspects, making it impossible to fully utilize the performance advantages of composite carbide ceramics in actual engineering applications.
[0006] Therefore, how to precisely control the structure of the composite carbide ceramic bulk material to obtain composite carbide ceramics with high mechanical properties is an urgent problem to be solved. Summary of the invention
[0007] In view of this, the present invention provides a method for preparing a compound carbide ceramic by spinodal decomposition hardening. The compound carbide ceramic block material is subjected to an aging treatment at a specific temperature to cause spinodal decomposition, thereby obtaining a compound carbide ceramic with higher mechanical properties.
[0008] In a first aspect, the present invention provides a method for preparing a spinodal decomposition hardening composite carbide ceramic, comprising the following steps:
[0009] A transition metal source, a titanium source and a zirconium source or a titanium source, a zirconium source and a hafnium source are mixed and dissolved in a solvent, a carbon source and a complexing agent are added, stirred and dispersed, and then heated and stirred to form a wet gel, which is dried, crushed and then heat-treated to obtain a compound carbide powder; the compound carbide powder is rapidly hot-pressed and sintered to obtain a compound carbide ceramic block material; and the compound carbide ceramic block material is aged at 1350-1450°C for 2-4h to obtain the compound carbide ceramic block material.
[0010] Preferably, the zirconium source includes zirconium oxychloride, zirconium chloride or zirconium nitrate; the titanium source includes titanium chloride, titanium sulfate or titanium nitrate; and the hafnium source includes hafnium chloride, hafnium nitrate or hafnium sulfate.
[0011] Preferably, when the transition metal source is a titanium source and a zirconium source, the molar ratio of titanium to zirconium is 0.2 to 4:1; when the transition metal source is a titanium source, a zirconium source and a hafnium source, the molar ratio of titanium, zirconium and hafnium is titanium: (hafnium + zirconium) = 0.2-4:1.
[0012] Preferably, the solvent is ethanol; the complexing agent is citric acid, oxalic acid, tartaric acid or gluconic acid; and the molar ratio of the total mole of the transition metal source to the citric acid is 3 to 5:1.
[0013] Preferably, the carbon source comprises one or more of glucose, sugar alcohol, sucrose or phenolic resin. The molar ratio of the total mole of the transition metal source to the carbon source is 1 to 3:1.
[0014] Preferably, the stirring and dispersing time is 1 to 3 hours; in the heating and stirring step to form a wet gel, the heating temperature is 60 to 80° C. and the heating time is 2 to 4 hours.
[0015] Preferably, the drying temperature is 70-90° C., the drying time is 5-8 hours, and the powder particle size obtained by crushing is 500-1000 nm.
[0016] Preferably, the heating rate of the heat treatment is 5-10°C / min, the heat treatment temperature is 1480-1550°C, and the time is 2-4h.
[0017] Preferably, the rapid hot pressing sintering has a heating rate of 70 to 90° C. / min, a temperature of 1700 to 1900° C., a time of 4 to 8 min, and a pressure of 20 to 40 MPa.
[0018] In a second aspect, the present invention provides a spinodal decomposition hardened composite carbide ceramic prepared by the above preparation method.
[0019] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0020] (1) The carbide powder prepared by the sol-gel method of the present invention has the characteristics of small particle size and good particle dispersibility. The electric field assisted by rapid hot pressing sintering enables it to synthesize composite carbide ceramic materials at a lower temperature; the sample after specific aging treatment shows the phenomenon of spinodal decomposition, and with the occurrence of this phenomenon, the hardness is significantly improved;
[0021] (2) The process provided by the present invention is simple and easy to control, the formation mechanism is clear and definite, and it has high industrial application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0023] Figure 1 1 is the XRD diagram of the composite carbide ceramics of Comparative Examples 1 to 3 and Examples 1 to 3 of the present invention;
[0024] Figure 2 The present invention is a surface scanning electron microscope image of the compound carbide ceramics of Examples 1 to 3 and Comparative Examples 1 to 3; wherein, a: Comparative Example 1; b, Comparative Example 2; c, Comparative Example 3; d, Example 1; e, Example 2; f, Example 3. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0026] The present invention provides a method for preparing a spinodal decomposition hardening composite carbide ceramic, comprising the following steps:
[0027] A transition metal source, a titanium source and a zirconium source or a titanium source, a zirconium source and a hafnium source are mixed and dissolved in a solvent, a carbon source and a complexing agent are added, stirred and dispersed, and then heated and stirred to form a wet gel, which is dried, crushed and then heat-treated to obtain a compound carbide powder; the compound carbide powder is rapidly hot-pressed and sintered to obtain a compound carbide ceramic block material; and the compound carbide ceramic block material is aged at 1350-1450°C for 2-4h to obtain the compound carbide ceramic block material.
[0028] The inventors found that after the composite carbide ceramic block material was subjected to an aging treatment for a specific time and a specific temperature, a spinodal decomposition phenomenon occurred, and the performance of the resulting composite carbide ceramic was significantly improved compared to the composite carbide ceramic that had not been subjected to an aging treatment. When the aging treatment temperature is too high or the time is too long, the grains are coarse, which has an adverse effect on the improvement of performance; when the aging treatment temperature is too low or the time is too short, the spinodal decomposition phenomenon cannot occur. That is, a composite carbide ceramic block material with improved performance can be obtained by aging treatment at a specific temperature and a specific time.
[0029] In the present invention, the zirconium source includes zirconium oxychloride, zirconium chloride or zirconium nitrate; the titanium source includes titanium chloride, titanium sulfate or titanium nitrate; the hafnium source includes hafnium chloride, hafnium nitrate or hafnium sulfate. The purity of the raw materials of the selected transition metal sources is above 99%. When the transition metal sources are titanium source and zirconium source, the molar ratio of titanium to zirconium is 0.2-4:1; when the transition metal sources are titanium source, zirconium source and hafnium source, the molar ratio of titanium, zirconium and hafnium is titanium: (hafnium + zirconium) = 0.2-4:1. Spinodal decomposition can occur within the above composition range.
[0030] In the present invention, the solvent is ethanol. The use of ethanol can expand the transition metal source used and avoid the problem that some salts are easily hydrolyzed. The complexing agent is citric acid, oxalic acid, tartaric acid or gluconic acid; the total molar ratio of the transition metal source to citric acid is 3 to 5:1. The addition of the complexing agent enhances the stability of the complexing reaction.
[0031] In the present invention, the carbon source includes one or more of glucose, sugar alcohol, sucrose or phenolic resin. The molar ratio of the total mole of the transition metal source to the carbon source is 1 to 3:1.
[0032] The stirring and dispersing time of the present invention is 1 to 3 hours; in the heating and stirring step to form a wet gel, the heating temperature is 60 to 80° C. and the heating time is 2 to 4 hours. The precursor is prepared by the sol-gel method to achieve the combination of various elements at the ionic level.
[0033] In the present invention, the drying temperature is 70-90°C and the drying time is 5-8h. The dried gel obtained after drying is easily broken into powder, which is beneficial for subsequent heat treatment. The present invention does not impose any special restrictions on the method of breaking, and the commonly used breaking means in the art can be used. The powder particle size obtained by breaking in the present invention is 500-1000nm.
[0034] In the present invention, the heating rate of the heat treatment is 5-10°C / min, the heat treatment temperature is 1480-1550°C, and the time is 2-4h. The compound carbide powder obtained after the heat treatment has the advantages of small grain size, high purity and uniform distribution of various elements.
[0035] In the present invention, the temperature of rapid hot pressing sintering is 1700-1900°C, the time is 4-8 minutes, and the pressure is 20-40MPa. Rapid hot pressing sintering technology can significantly reduce the sintering temperature with the assistance of a large current (about 2500A), and the compound carbide powder is converted into a compound carbide ceramic block material through rapid hot pressing sintering.
[0036] The present invention also provides a spinodal decomposition hardening compound carbide ceramic prepared by the above preparation method. The spinodal decomposition hardening compound carbide ceramic has high hardness and good mechanical properties.
[0037] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0038] Example 1
[0039] This embodiment provides a method for preparing a composite carbide ceramic by spinodal decomposition hardening, and the specific steps are as follows:
[0040] (1) Prepare raw material powder: Ti: Zr = 0.43: 1, put 22.54g ZrOCl2·8H2O (0.07mol) and 7.2g TiCl4 (0.03mol) into 50mL ethanol, stir on a magnetic stirrer until completely dissolved, put 9g glucose (0.05mol) into the solvent, continue stirring until dissolved. Then add 4.8g citric acid (0.025mol) as a complexing agent, the solution will turn into a light yellow solution during stirring, continue stirring for 2h to obtain a better dispersion effect.
[0041] (2) Place the stirred solution in a 70°C water bath for heating and stirring. Continue stirring for 3 hours. The solution will turn into a brown-yellow gel.
[0042] (3) Place the gel in an oven at 80°C to dry completely.
[0043] (4) After the dried gel is crushed and ground, it is heat treated in a tubular furnace at a heating rate of 8°C / min and a holding time of 3 h at 1500°C to obtain a carbide powder with a small particle size and uniform mixing.
[0044] (5) The obtained carbide powder is ground and then rapidly hot-pressed and sintered at a heating rate of 80°C / min and kept at 1800°C for 5 min to obtain a composite carbide ceramic block material.
[0045] (6) The obtained composite carbide ceramic material is subjected to aging treatment at 1400° C. for 3 h in a tubular furnace to obtain a composite carbide ceramic.
[0046] Example 2
[0047] This embodiment provides a method for preparing a composite carbide ceramic by spinodal decomposition hardening, and the specific steps are as follows:
[0048] (1) Prepare raw material powder: Ti:Zr = 1:1, put 16.1g ZrOCl2·8H2O (0.05mol) and 12.0g TiCl4 (0.05mol) into 50mL ethanol, stir on a magnetic stirrer until completely dissolved, put 9g glucose (0.05mol) into the solvent, continue stirring until dissolved. Then add 4.8g citric acid (0.025mol) as a complexing agent, the solution will turn into a light yellow solution during stirring, continue stirring for 2h to obtain a better dispersion effect.
[0049] (2) Place the stirred solution in a 70°C water bath for heating and stirring. Continue stirring for 3 hours. The solution will turn into a brown-yellow gel.
[0050] (3) Place the gel in an oven at 80°C to dry completely.
[0051] (4) The dried gel is crushed and ground, and then heat-treated in a tubular furnace at a heating rate of 8°C / min and a holding time of 3 h at 1500°C to obtain a carbide powder with a small particle size and uniform mixing.
[0052] (5) The obtained carbide powder is ground and then rapidly hot-pressed and sintered at a heating rate of 80°C / min and kept at 1800°C for 5 min to obtain a carbide bulk material.
[0053] (6) The obtained composite carbide ceramic material is subjected to aging treatment in a tubular furnace at 1400°C for 3 h.
[0054] Example 3
[0055] This embodiment provides a method for preparing a composite carbide ceramic by spinodal decomposition hardening, and the specific steps are as follows:
[0056] (1) Prepare raw material powder: Ti: (Zr + Hf) = 0.67:1, put 12.88g ZrOCl2·8H2O (0.04mol), 9.6g TiCl4 (0.04mol) and 6.41g HfCl4 (0.02mol) into 50mL ethanol, stir on a magnetic stirrer until completely dissolved, put 9g glucose (0.05mol) into the solvent, continue stirring until dissolved. Then add 4.8g citric acid (0.025mol) as a complexing agent. During the stirring process, the solution will turn into a light yellow solution. Continue stirring for 2h to obtain a better dispersion effect.
[0057] (2) Place the stirred solution in a 70°C water bath for heating and stirring. Continue stirring for 3 hours. The solution will turn into a brown-yellow gel.
[0058] (3) Place the gel in an oven to dry completely.
[0059] (4) The dried gel is crushed and ground, and then heat-treated in a tubular furnace at a heating rate of 8°C / min and a holding time of 3 h at 1500°C to obtain a carbide powder with a small particle size and uniform mixing.
[0060] (5) The obtained carbide powder is ground and then rapidly hot-pressed and sintered at a heating rate of 80°C / min and kept at 1800°C for 5 min to obtain a carbide bulk material.
[0061] (6) The obtained composite carbide ceramics were subjected to aging treatment in a tubular furnace at 1400°C for 3 h.
[0062] Example 4
[0063] Compared with Example 1, the difference is that in this example, the obtained composite carbide ceramic is subjected to aging treatment at 1400° C. for 2.5 hours in a tubular furnace.
[0064] Example 5
[0065] Compared with Example 1, the difference is that in this example, the obtained composite carbide ceramic is subjected to aging treatment at 1400° C. for 3.5 hours in a tubular furnace.
[0066] Example 6
[0067] Compared with Example 1, the difference is that in this example, the obtained composite carbide ceramic is subjected to aging treatment at 1350° C. for 3 hours in a tubular furnace.
[0068] Example 7
[0069] Compared with Example 1, the difference is that in this example, the obtained composite carbide ceramic is subjected to aging treatment in a tubular furnace at 1450° C. for 3 hours.
[0070] Example 8
[0071] Compared with Example 1, the difference is that in this example, Ti: (Zr + Hf) = 1: 1. 16.1 g of ZrOCl2·8H2O (0.05 mol), 9.6 g of TiCl4 (0.04 mol) and 3.205 g of HfCl4 (0.01 mol) were placed in 50 mL of ethanol.
[0072] Comparative Example 1
[0073] Compared with Example 1, this comparative example does not perform the aging treatment in step (6).
[0074] Comparative Example 2
[0075] Compared with Example 2, this comparative example does not perform the aging treatment in step (6).
[0076] Comparative Example 3
[0077] Compared with Example 3, this comparative example does not perform the aging treatment in step (6).
[0078] Comparative Example 4
[0079] Compared with Example 8, this comparative example does not perform the aging treatment in step (6).
[0080] Comparative Example 5
[0081] Compared with Example 1, in this comparative example, the obtained compound carbide ceramic material was subjected to aging treatment at 1500° C. for 3 h in a tubular furnace to obtain a compound carbide ceramic.
[0082] Comparative Example 6
[0083] Compared with Example 1, in this comparative example, the obtained compound carbide ceramic material was subjected to aging treatment at 1300° C. for 3 h in a tubular furnace to obtain a compound carbide ceramic.
[0084] Comparative Example 7
[0085] Compared with Example 1, in this comparative example, the obtained compound carbide ceramic material was subjected to aging treatment at 1400° C. for 6 hours in a tube furnace to obtain a compound carbide ceramic.
[0086] Comparative Example 8
[0087] Compared with Example 1, the obtained composite carbide ceramic material in this comparative example was subjected to aging treatment at 1400° C. for 1 h in a tube furnace to obtain a composite carbide ceramic. The composite carbide ceramic prepared in this comparative example did not show spinodal decomposition.
[0088] Test example
[0089] For Examples 1 to 3 ( Figure 1 B) and Comparative Examples 1 to 3 ( Figure 1 A) The obtained composite carbide ceramics were subjected to X-ray diffraction (XRD) test, as shown in FIG. Figure 1 As shown in the XRD diagram, it can be seen that the complex carbides have been synthesized, and the peaks after aging treatment show obvious peak separation, which verifies the successful preparation of the sample and the smooth progress of the aging treatment.
[0090] For Examples 1 to 3 ( Figure 2 d~f) and Comparative Examples 1~3 ( Figure 2 The composite carbide ceramics of a~c) were measured by surface scanning electron microscopy. Figure 2 As shown in the figure, it can be seen that the comparative examples 1 to 3 without aging treatment did not show the spinodal decomposition phenomenon, while the examples 1 to 3 after aging treatment at 1400° C. for 3 hours showed the spinodal decomposition phenomenon.
[0091] The hardness of the composite carbide ceramics obtained in Examples 1 to 8 and Comparative Examples 1 to 7 was measured with a load of 10 N and a holding time of 15 s. The results are shown in Table 1.
[0092] Table 1 Test results of composite carbide ceramic properties of Examples 1 to 8 and Comparative Examples 1 to 7
[0093]
[0094]
[0095] From the comparison of the above data, it can be found that the hardness of the samples after aging treatment at 1350-1450℃ for 2.5-3.5h is significantly improved, especially for Ti, Zr binary compound carbide ceramics, the hardness improvement can reach up to 15%. Although the hardness improvement of Ti, Zr, Hf ternary compound carbide ceramics is relatively low, after aging treatment, the hardness can be as high as 2280Hv or more, and it has excellent mechanical properties. Comparative Examples 5-7 also showed spinodal decomposition, but the aging treatment temperature was too high (1500℃) or the aging treatment time was too long (6h), and the grains were coarse, resulting in an insignificant hardness improvement, and the improvement was less than 5%. When the aging treatment temperature was too low (1300℃), the spinodal decomposition was incomplete, so the performance improvement was not high, less than 5%. When the aging treatment time was too short (1h), the decomposition was incomplete, and spinodal decomposition was not observed in Comparative Example 8, so the hardness improvement was very small. It can be seen that precise control of the aging time and aging temperature is required to significantly improve the performance of the final composite carbide ceramics.
[0096] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a spinodal decomposition hardening composite carbide ceramic, characterized in that: The steps include: A transition metal source, a titanium source and a zirconium source or a titanium source, a zirconium source and a hafnium source are mixed and dissolved in a solvent, a carbon source and a complexing agent are added, stirred and dispersed, and then heated and stirred to form a wet gel, which is dried, crushed and heat-treated to obtain a compound carbide powder; the compound carbide powder is rapidly hot-pressed and sintered to obtain a compound carbide ceramic block material; the compound carbide ceramic block material is subjected to aging treatment at 1350-1450° C. for 2-4 hours to obtain a composite carbide ceramic block material; The zirconium source includes zirconium oxychloride, zirconium chloride or zirconium nitrate; the titanium source includes titanium chloride, titanium sulfate or titanium nitrate; the hafnium source includes hafnium chloride, hafnium nitrate or hafnium sulfate; When the transition metal source is a titanium source and a zirconium source, the molar ratio of titanium to zirconium is 0.2-4:1; when the transition metal source is a titanium source, a zirconium source and a hafnium source, the molar ratio of titanium, zirconium and hafnium is titanium: (hafnium + zirconium) = 0.2-4:1; The rapid hot pressing sintering has a heating rate of 70-90°C / min, a temperature of 1700-1900°C, a time of 4-8min, and a pressure of 20-40MPa.
2. The preparation method according to claim 1, characterized in that The solvent is ethanol; the complexing agent is citric acid, oxalic acid, tartaric acid or gluconic acid; and the molar ratio of the total mole of the transition metal source to the citric acid is 3-5:
1.
3. The preparation method according to claim 1, characterized in that: The carbon source comprises one or more of glucose, sugar alcohol, sucrose or phenolic resin; the molar ratio of the total mole of the transition metal source to the carbon source is 1 to 3:
1.
4. The preparation method according to claim 1, characterized in that: The stirring and dispersing time is 1 to 3 hours; in the heating and stirring step to form a wet gel, the heating temperature is 60 to 80° C. and the heating time is 2 to 4 hours.
5. The preparation method according to claim 1, characterized in that: The drying temperature is 70-90° C., and the drying time is 5-8 hours. The particle size of the powder obtained by crushing is 500-1000 nm.
6. The preparation method according to claim 1, characterized in that: The heating rate of the heat treatment is 5-10°C / min, the temperature of the heat treatment is 1480-1550°C, and the time is 2-4h.
7. The spinodal decomposition hardening composite carbide ceramic prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Medium-entropy or high-entropy carbide nano-powder and preparation method thereof
CN116947497A
Transition metal carbonitride high-entropy ceramic as well as preparation method and application thereof
CN110590372A
Ultrahigh-temperature high-entropy carbide powder and preparation method thereof
CN112851352A
Titanium carbonitride-based solid solution particle reinforced high-temperature wear-resistant coating and preparation method thereof
CN116607096A
Cited By
Method for inducing amplitude decomposition of high-entropy carbide ceramics by plasma sintering
CN122608418A